Directions of development of the services on the basis of modern marketing strategies - Radjabov Bunyod Abduhalilovich (Universitas Muhammadiyah Sidoarjo, 2019)
The main problems of development of the services market in the Republic of Uzbekistan are considered in the article. Based on the strategic analysis of the BCG matrix, the development of the services market in the regions is analyzed. Based on the results of the strategic analysis, recommendations for the development of the market of services in the regions of the republic on marketing strategy have been developed